Sistem Pendukung Keputusan Analisa Kinerja Instruktur (Honorer) Balai Besar Pelatihan Vokasi Dan Produktivitas (BBPVP) Medan Dengan Metode Weighted Product (WP) - Utami, Destia Nada; Latersia, Egya Dora; Tri Amisri, Nurul Hasanah; Lubis, Riri Syafitri (Unity Academy, 2025)
The performance evaluation of honorary instructors at BBPVP Medan is often subjective and lacks a measurable assessment system. This activity aims to design a decision support system to objectively evaluate instructor performance using the Weighted Product (WP) method. The evaluation criteria include attendance (40%), work discipline (35%), and teamwork (25%). Data were collected through observation, interviews, and documentation involving ten honorary instructors. The WP calculation results show that the instructor named Darmanto Koemardy achieved the highest score (0.189) and is recommended for contract extension. The application of the WP method improves the objectivity and efficiency of performance evaluations for instructors at BBPVP Medan.